Analisis Faktor-Faktor yang Mempengaruhi Usaha Tani Padi Sawah Studi Kasus: Desa Pulau Pandan Kecamatan Limun Kabupaten Sarolangun - Ilmiyati Ilmiyati; Junaidi Junaidi; Adi Bhakti (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2017)
The study aims to analyze : (1) characteristics of farmers and land rice farming in the Village of Pulau Pandan; (2) production and income of farmers in in the Village of Pulau Pandan; and (3) factors affecting the production of wet land paddy farming in the Village of Pulau Pandan.Based on the results of the research, it is known that simultaneously (factors) : the area of land, seeds, fertilizer, and pesticide have a significant effect or rice production in Pulau Pandan Village, and partially significant factor on rice production rice fields are land area and pesticide while seeds and fertilizer have no significant effect .the value of coefficient of determination is 0,960 which means the dependent variable (production) can be explained by the independent variable (land area, seeds, fertilizer, and pesticide) of 96% and the rest of 4% is explained by other variables not included in the model. The average income of paddy field farming is quite high for every planting season that is Rp. 19.317.480/Hectare